A new method for intermediate power point tracking for PV generator under partially shaded conditions in hybrid system - Guichi, Amar; Talha, Abdelaziz; Berkouk, El Madjid; Mekhilef, Saad; Gassab, Samir (Elsevier, 2018)
The tracking of the Intermediate Power Point is more important than the Maximum Power Point when the photovoltaic system becomes a part of a hybrid power generation system. It means that the photovoltaic system can either work on the Maximum Power Point or on the Intermediate Power Point. An optimized control technique for hybrid power generation system is developed in this study to work in both cases with high accuracy and good efficiency, under normal or partially shaded conditions. This technique is based on the combination of two algorithms, the particle swarm optimization algorithm for tracking the global maximum power point, while a newly developed algorithm is used for attaining any other supervisory control set point. Furthermore, the new proposed algorithm has the advantage of choosing the point of highest voltage and lower current among the other points that provide the same power, which would increase the efficiency of the system by reducing the power losses. A simulation work is carried out to assess the effectiveness of the proposed technique. Different scenarios under normal and partially shaded conditions are verified. Finally, the combined control algorithm was implemented using a DSpace 1104 environment and extensively tested under various partially shaded patterns. The experimental results of the prototype have proven that the newly developed algorithm improves the capability of photovoltaic system to response quickly and precisely to the supervisor of the hybrid power system under different partially shaded conditions.